2012
DOI: 10.3146/ps11-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration Response to Vapor Pressure Deficit in Field Grown Peanut

Abstract: Water deficit, i.e., rainfall amounts and distribution, is the most common abiotic stress that limits peanut production worldwide. Even though extensive research efforts have been made to improve drought tolerance in peanut, performance of genotypes largely depends upon the environment in which they grow. Based on greenhouse experiments, it has been hypothesized that stomata closure under high vapor pressure deficit (VPD) is a mechanism of soil water conservation and it has been shown that genotypic variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In this study, we observed similar variation of the VPD (leaf-air) in plants in both regions, with a peak above 5.0 KPa at 12:00 p.m. At this hour, plants in the semi-arid region showed an inverse correlation between VPD (leaf-air) and stomatal conductance, transpiration, and photosynthesis, which must have been influenced by high temperatures and low soil water availability on the site, these factors probably, increased the effect of VPD (leaf-air) in stomatal closure and consequent reduction in transpiration to prevent water loss. Similar results were also found in different cultures, such as sugar-apples (Endres 2007), peanuts (Balota et al 2012), and purging nut (Santos et al 2013), in which, in studies conducted during the dry season, the authors also found that the increase in vapor pressure deficit in the early afternoon negatively influenced the stomatal conductance in these species.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we observed similar variation of the VPD (leaf-air) in plants in both regions, with a peak above 5.0 KPa at 12:00 p.m. At this hour, plants in the semi-arid region showed an inverse correlation between VPD (leaf-air) and stomatal conductance, transpiration, and photosynthesis, which must have been influenced by high temperatures and low soil water availability on the site, these factors probably, increased the effect of VPD (leaf-air) in stomatal closure and consequent reduction in transpiration to prevent water loss. Similar results were also found in different cultures, such as sugar-apples (Endres 2007), peanuts (Balota et al 2012), and purging nut (Santos et al 2013), in which, in studies conducted during the dry season, the authors also found that the increase in vapor pressure deficit in the early afternoon negatively influenced the stomatal conductance in these species.…”
Section: Discussionsupporting
confidence: 71%
“…Eight virginia-type peanut genotypes including commercial cultivars (Bailey, CHAMPS, and Phillips) and advanced breeding lines (N04074FCT, N05006, N05008, N05024J, and SPT 06-07) were selected from the Peanut Variety and Quality Evaluation (PVQE) program based on earlier field evaluations and contrasting leaf gas exchange patterns in response to water stress and vapor pressure deficit (VPD) (Balota et al, 2012a(Balota et al, , 2012b. Eight virginia-type peanut genotypes including commercial cultivars (Bailey, CHAMPS, and Phillips) and advanced breeding lines (N04074FCT, N05006, N05008, N05024J, and SPT 06-07) were selected from the Peanut Variety and Quality Evaluation (PVQE) program based on earlier field evaluations and contrasting leaf gas exchange patterns in response to water stress and vapor pressure deficit (VPD) (Balota et al, 2012a(Balota et al, , 2012b.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Experiments were conducted on a Eunola loamy fine sand soil (fine-loamy, siliceous, semiactive, thermic Aquic Hapludult) at the Tidewater Agricultural Research and Extension Center, Suffolk, VA (36°68′N, 76°77′W; 25-m elevation) in 2011 and 2012 under rainfed and irrigated field conditions. Eight virginia-type peanut genotypes including commercial cultivars (Bailey, CHAMPS, and Phillips) and advanced breeding lines (N04074FCT, N05006, N05008, N05024J, and SPT 06-07) were selected from the Peanut Variety and Quality Evaluation (PVQE) program based on earlier field evaluations and contrasting leaf gas exchange patterns in response to water stress and vapor pressure deficit (VPD) (Balota et al, 2012a(Balota et al, , 2012b. In earlier studies, Phillips, Bailey, and N05024J showed high and CHAMPS, N04047FCT, N05006, and N05008 low stomatal conductance and CO 2 assimilation under water deficit stress in the field.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…In those terms, species with more effective stomatal control are expected to have a higher chance of survival in the upcoming climate change (HAWORTH et al, 2011). Another strategy of plants pressured by unfavorable conditions is facilitated through stomata behavior, which presents a short turn-reaction when experiencing drought stress (LUAN, 2002;MARTIN-STPAUL et al, 2017), salinity (MUNNS and TESTER, 2008;SOLMAZ et al, 2011), a high CO2 concentration (YOUNG et al, 2006;ENGINEER et al, 2014) or a vapor pressure deficit (BALOTA et al, 2012;MCADAM et al, 2016). For instance, when in water deficit, plants can react by closing their stomata when water supply is limited (ZWIENIECKI et al, 2016).…”
Section: Introductionmentioning
confidence: 99%